Toward an Integrated Framework in Health and Human Rights Education: Transformative Pedagogies in Social Medicine, Collective Health, and Structural Competency - Luis Martin Ortega; Michael J. Westerhaus; Amy Finnegan; Aarti Bhatt; Alex Olirus Owilli; Brian Turigye; Youri Encelotti Louis (Health and Human Rights, 2023)
Global health equity is at a historically tenuous nexus complicated by economic inequality, climate change, mass migration, racialized violence, and global pandemics. Social medicine, collective health, and structural competency are interdisciplinary fields with their own histories and fragmentary implementation in health equity movements situated both locally and globally. In this paper, we review these three fields’ historical backgrounds, theoretical underpinnings, and contemporary contributions to global health equity. We believe that intentional dialogue between these fields could promote a generative discourse rooted in a shared understanding of their historical antecedents and theoretical frameworks. We also propose pedagogical tools grounded within our own critical and transformative pedagogies that offer the prospect of bringing these traditions into greater dialogue for the purpose of actualizing the human right to health.